Impact of Liquidity, Profitability, and Capital Structure on Firm Value by Organizational Size: The Company as a Control Variable - Nova Ayuk Setyowati; Wuryaningsih Dwi Lestari (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research initiative seeks to evaluate the influence of liquidity, profitability, and capital structure on the valuation of firms, incorporating company size as a control variable within the manufacturing domain of the food and beverage subsector listed on the Indonesia Stock Exchange (BEI). The dataset comprises the annual financial reports of the companies for the period spanning 2021 to 2023. The sample selection was executed through purposeful sampling, yielding 123 observations from 41 companies over a three-year timeframe. Data analysis was conducted via a panel data regression methodology, utilizing E-Views 12 software. Results indicated that liquidity (CR) and ROA exerted a significant positive influence on PBV, while capital structure (DER) was found to be statistically insignificant with respect to PBV. Collectively, the three independent variables explained 30.86% of the variance in the firm's valuation, with the remaining 69.14% ascribable to factors beyond the scope of the research model.